XÁC ĐỊNH HÀM LƯỢNG ACID PERFLOROOCTAN SULFONIC TRONG MẪU NƯỚC BẰNG PHƯƠNG PHÁP SẮC KÝ LỎNG KHỐI PHỔ - Nguyễn, Kim Thuỳ; Hán, Duy Linh; Nguyễn, Thị Năng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DETERMINATION OF PERFLUOROOCTANE SULFONIC ACID (PFOS) IN WATER BY LIQUID CHROMATOGRAPHYThis study used liquid - liquid extraction (LLE) and liquid chromatography Triple Quadrupole Tandem Mass Spectrometry (LC/MS/MS) Agilent 6430 Triple Quad to survey and assessment PFOS contamination in water. The optimistical conditions are: Product ion is m/z = 80 for quantification and m/z = 98.9 to qualifier; collision energy (CE) is 80V, mobile phase is 80% methanol and 20% amonium acetate 5mM. Base on these conditions, PFOS in 1.0 L water is determined by LLE three times with 100 ml DCM. This process has LOD = 0.2 ng/L; LOQ = 1 ng/L; RSD < 21% and recovery > 80%. The results are suitable to requirements of AOAC to analyse PFOS in water samples.